2006
DOI: 10.1523/jneurosci.3561-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic Inputs to the Bed Nucleus of the Stria Terminalis and Paraventricular Nucleus of the Hypothalamus Underlie Hypothalamic–Pituitary–Adrenal Axis But Not Hypophagic or Conditioned Avoidance Responses to Systemic Yohimbine

Abstract: The ␣2 adrenoceptor antagonist yohimbine (YO) increases transmitter release from adrenergic/noradrenergic (NA) neurons. Systemic YO activates the hypothalamic-pituitary-adrenal (HPA) axis, inhibits feeding, and supports conditioned flavor avoidance (CFA) in rats. To determine whether these effects require NA inputs to the bed nucleus of the stria terminalis (BNST), vehicle or saporin toxin conjugated to an antibody against dopamine ␤ hydroxylase (DSAP) was microinjected bilaterally into the BNST to remove its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
87
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 59 publications
9
87
0
Order By: Relevance
“…Similar preliminary results have been obtained in toxin-lesioned rats subsequently treated with systemic lithium chloride (LiCl) (Figure 2). Conversely, inputs to magnocellular regions of the PVN and SON appear to arise from medullary NA neurons that do not also project to either the BNST or the PVNmp [102]. This finding complements previous evidence that magnocellular and parvocellular PVN subdivisions are differentially innervated by NA inputs arising from the VLM and NST, respectively [91].…”
Section: Viscerosensory Inputs To the Endocrine Hypothalamus Are Primsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar preliminary results have been obtained in toxin-lesioned rats subsequently treated with systemic lithium chloride (LiCl) (Figure 2). Conversely, inputs to magnocellular regions of the PVN and SON appear to arise from medullary NA neurons that do not also project to either the BNST or the PVNmp [102]. This finding complements previous evidence that magnocellular and parvocellular PVN subdivisions are differentially innervated by NA inputs arising from the VLM and NST, respectively [91].…”
Section: Viscerosensory Inputs To the Endocrine Hypothalamus Are Primsupporting
confidence: 84%
“…Immunotoxic lesioning methods have demonstrated that these NA inputs are necessary for systemic yohimbine (a sympathomimetic adrenergic signal-enhancing drug) to activate neural expression of the immediate-early gene product, Fos, in CRF neurons within the PVNmp, and to increase plasma corticosterone levels [102]. Similar preliminary results have been obtained in toxin-lesioned rats subsequently treated with systemic lithium chloride (LiCl) (Figure 2).…”
Section: Viscerosensory Inputs To the Endocrine Hypothalamus Are Primmentioning
confidence: 57%
See 1 more Smart Citation
“…Microdialysis studies have demonstrated that NE levels remain elevated above the baseline in the BNST over an hour after restraint stress and blocking a 1 -ARs attenuates stress-induced rises in adrenocorticotropic hormone (ACTH) (Pacak et al, 1995;Cecchi et al, 2002). Moreover, Banihashemi and Rinaman (2006) showed that ablating BNST NE inputs prevents increases in corticosterone to i.p. yohimbine 90 min post injection.…”
Section: Ne Induces Ltd In a Time-dependent Mannermentioning
confidence: 99%
“…a 1 -ARs in the BNST modulate ACTH levels in animals who have been exposed to a stressor (Cecchi et al, 2002). Moreover it has recently been shown that the same axon collaterals from the nucleus tractus solitarius that project to the BNST also may project to the PVN (Banihashemi and Rinaman, 2006). NE may therefore modulate this circuitry regardless of input from cortical structures.…”
Section: Ne Induces Ltd In a Time-dependent Mannermentioning
confidence: 99%